The Effectiveness of Self Hypnosis and Slow deep Breathing on Labor Pain in Midwife Independent Practice - Sumastri, Heni; Novita, Nesi; Yuka, Aprilia Ayu Shinta; Martini, Sri; Setiawati, Desy (Journal of Maternal and Child Health Sciences (JMCHS), 2025)
Background: Labor pain arises due to stretching of the uterus which will affect the body's activities as a whole, for example increased oxygen demand, increased ventilation, increased blood pressure and digestive system disorders. One of the methods needed by mothers in facing the birthing process is the self-Hypnosis and Slow Deep Breathing technique which aims to enable mothers to give birth comfortably, quickly and smoothly and reduce or eliminate pain during childbirth without the help of analgesic drugs. This method also places more emphasis on birth in a positive, gentle, safe and easy way. Objective: This research aims to determine the effect of self hypnosis and Slow Deep Breathing on labor pain in partu mothers during the first active phase in PMB Palembang City in 2024. Methods: This research is a quasi-experimental design with a non-equivalent control group design, sampling using using accidental sampling consisting of a control and treatment group, each consisting of 20 in-partu mothers at PMB Lismarini and 20 people at PMB Teti Herawati Palembang from April to May 2024. The data used is secondary data and primary data. Data were analyzed using the Independent T test. Results: There is an influence of Self Hypnosis and Slow Deep Breathing on maternal labor pain during one active phase in Palembang City PMB in 2024 (ρ=0.000). Conclusion: There is an influence of Self Hypnosis and Slow Deep Breathing on labor pain in in-partum mothers during one active phase.